Effect of add‐on melatonin on seizure outcomes and quality of sleep in epilepsy with idiopathic generalized tonic‐clonic seizures alone in adult patients: Cross‐sectional, randomized, double‐blind, placebo‐controlled clinical trial. Issue 2 (1st January 2023) - Maghbooli, Mehdi; Alyan NajafAbadi, Somayeh; MalekMahmoudi, Ghazal; Molseghi, Mohammad Hadi
Abstract: Background: Effective treatment of epilepsy is a major challenge in the field of neurology. Studies have suggested that melatonin can work in epilepsy with a good safety profile. Objectives: This study was performed to determine the effectiveness of melatonin in seizure outcomes, as well as the quality of sleep in patients with generalized epilepsy. Methods: In this cross‐over clinical trial study, 60 patients with epilepsy with idiopathic generalized tonic‐clonic seizures alone (EGTCS) and under valproic acid treatment received either melatonin or placebo with a washout period of 2 weeks intermittently. Outcome variables included a reduction in the severity and frequency of epilepsy besides improvement in electroencephalogram (EEG) abnormalities and sleep quality. Results: By adding melatonin, a decrease in the mean severity score of epilepsy (according to the Chalfont questionnaire) was 32.33 ± 9.24, while it was 5.58 ± 14.28 in treatment with placebo ( p = .002). Evaluation of the number of attacks and EEG results did not disclose any therapeutic efficacy in treatment with melatonin versus placebo. The quality of sleep improved in 40% (first round) and 53.4% (second round) of subjects who received melatonin ( p < .001). Conclusions: Considering that the addition of melatonin to routine anti‐seizure treatment was effective in reducing the severity of epilepsy and improving sleep quality, it seems that melatonin can be useful as an adjunct therapy for EGTCS in well‐defined circumstances. Abstract : Recent data disclose that melatonin prevents seizures in animal models and could be effective and safe for decreasing epileptic manifestations in humans. This study indicated that the addition of melatonin to a routine antiepileptic regimen was effective in reducing the severity of epilepsy; it seems that melatonin can be used as an adjunct therapy for idiopathic generalized tonic‐clonic epilepsy in well‐defined circumstances.